Dermot Healy, Resourceful Playwright - Pilný, Ondřej (Hungarian Journal of English and American Studies, 2021)
Book review: Hopper, Keith, and Neil Murphy, eds. Dermot Healy: The Collected Plays. Victoria, TX: Dalkey Archive P, 2016. xxxiii + 583 pages. ISBN 978-1-56478-930-3. Pbk. 21.00/£15.00.